2003
DOI: 10.1523/jneurosci.23-17-06695.2003
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Critical Period Induction by Tonic Inhibition in Visual Cortex

Abstract: Mice lacking a synaptic isoform of glutamic acid decarboxylase (GAD65) do not exhibit ocular dominance plasticity unless an appropriate level of GABAergic transmission is restored by direct infusion of benzodiazepines into the brain. To better understand how intracortical inhibition triggers experience-dependent changes, we dissected the precise timing requirement for GABA function in the monocular deprivation (MD) paradigm. Diazepam (DZ) or vehicle solution was infused daily before and/or during 4 d of MD in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
154
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(161 citation statements)
references
References 56 publications
7
154
0
Order By: Relevance
“…In V1, BDNF (Hanover et al, 1999) and the development of GABAergic projections have been shown to play a key role in the onset of the critical period (Fagiolini and Hensch, 2000;Fagiolini et al, 2004). Similarly, dark-rearing delays the onset of the critical period (Mower, 1991;Iwai et al, 2003). Strikingly, once triggered, the critical period is always of a fixed duration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In V1, BDNF (Hanover et al, 1999) and the development of GABAergic projections have been shown to play a key role in the onset of the critical period (Fagiolini and Hensch, 2000;Fagiolini et al, 2004). Similarly, dark-rearing delays the onset of the critical period (Mower, 1991;Iwai et al, 2003). Strikingly, once triggered, the critical period is always of a fixed duration.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in the visual system of several species, the onset of monocular deprivation-related plasticity is closely linked to the completion of visual acuity development (Berardi et al, 2000(Berardi et al, , 2003Stern et al, 2001). Further supporting the concept that regulation of the CP window is tied to sensory experience, normally patterned inputs are necessary for the development of normal cortical columnar organization and the timing of CP offset (Fagiolini et al 1994;Zhang et al, 2002;Iwai et al 2003;Chang and Merzenich, 2003). This way, a premature closure of the CP could be prevented if insufficient or incoherent inputs are present during development.…”
Section: Introductionmentioning
confidence: 90%
“…Such possibilities may be further examined in developmental studies to compare the critical periods between wild-type and GAD67-GFP mice. In the visual cortex, enhancing or reducing tonic levels of GABA by diazepam (selective GABA agonist) infusion prematurely closes critical periods for monocular deprivation (Iwai et al, 2003).…”
Section: Network and Developmental Consequences Of Altered Intracortimentioning
confidence: 99%
“…In addition, benzodiazepine sensitivity was investigated in animals lacking the ability to synthesize GABA. The GAD65 knock-out mouse fails to enter the CP but can be made plastic by treating with the GABA agonist diaz-epam (DZ) (Hensch et al, 1998;Iwai et al, 2003). Natural CP timing can similarly be accelerated with DZ in immature wildtype mice (Fagiolini and Hensch, 2000).…”
Section: Inhibitory Plasticity In Sensory Systemsmentioning
confidence: 99%